The Role of Human Capital Investment in Developing Individual Performance - A Field Study at Hihayi Abdelmajid Qais Hospital, Khenchela Province - Zetouni , Ghenia; Aoufi , Mostefa (Social Sciences Journal)
This study examines the role of investment in human capital in enhancing individual performance within healthcare institutions, with a particular focus on the Haihi Abdelmajid Kaïs Hospital in Khenchela Province. The research aims to explore the relationship between human capital investment—through training, professional development, and motivation—and the performance of individuals within the healthcare institution. The descriptive-analytical method was employed by distributing questionnaires to 150 employees from various categories within the hospital, in addition to conducting interviews with administrators. The results revealed a positive relationship between training and professional development and individual performance, as well as between motivational strategies and individual performance. Moreover, the findings showed that increased investment in training and development enhances staff efficiency and leads to improved quality of healthcare services. The study recommends increasing investment in training programs, developing innovative motivational strategies, and integrating technology into training processes.